Night talks / Nur Ilianis Adnan, Noor Azli Affendy Lee and Nur Afiqah Abdul Latif - Adnan, Nur Ilianis; Affendy Lee, Noor Azli; Abdul Latif, Nur Afiqah (Academy of Language Studies, 2021)
The English Language Club conducted online LIVE talks via our English Language Club Youtube Channel by using StreamYard software. The talks can be considered as one of the initiatives taken by the club to promote the usage of English and to conduct intellectual interviews on social media.